Bodyweight-Related Polyandry in the Tobacco Cutworm Moth Spodoptera litura (Lepidoptera: Noctuidae). Issue 3 (22nd May 2019) - Xu, Jin; Chen, Zhe; Gao, Bo; Chen, Min; Fu, Da-Ying; Chen, Peng; Liu, Jian-Hong
Abstract: Recent studies on polyandry evolution have revolutionized our understanding of sexual selection. Therefore, study on traits in females, such as sensory perception and remating strategies, is expected to disclose a greater role of sexual selection in female evolution. Here, we tested how bodyweights of both sexes affected female and male remating behavior in Spodoptera litura (Fabricius, 1775) (Lepidoptera: Noctuidae). Results show most (74.4%; unmated virgin females may be sexually immature) females and males mated the first time in the second scotophase after eclosion. In the subsequent scotophase, 41.9% once-mated females and 94.1% once-mated males mated the second time with a novel virgin mate. Analyses indicate that female remating probability significantly increased with the increase of her own and the second male's bodyweight but decreased with the increase of the first male's bodyweight, while bodyweights of both sexes have no significant effect on male remating probability. Considering the nature of the low level of polyandry (two times on average) and last male precedence in S. litura, we propose that 1) females are more choosy when remating, from which females will benefit indirectly by sequential mate comparison and remate to replace sperm from the previous mates with those from higher quality mates, and 2) males will generally like to remate with any possible females, from which males will gain direct benefit by siring more offspring. The outcome of polyandry rate is likely to be the result of male investment × female choice interactions.